Utilization Of River Shell Waste (Lokan) As A mixture In Concrete: Pemanfaatan Limbah Cangkang Kerang Sungai (Lokan) Sebagai Bahan Campuran Pada Beton - Muhammad Nur Fajar; Herlina Arifin; Mohammad Aris; Alfina Maysyurah; Chandra Margareta (Universitas Negeri Surabaya, 2025)
The increasing need for concrete materials results in the availability of limestone as a non-renewable raw material for portland cement makers to be limited and will run out if its extraction is carried out continuously, so it is necessary to find replacement materials for cement as a constituent material for concrete. In this study, mussels shell waste was tested as a substitute for cement with a percentage of 2% and 5%. Furthermore, the parameters tested are compressive strength tests. Based on the test results, it was obtained that the compressive strength value decreased with the increase in the percentage of use of mashed shells.